PENINGKATAN KUALITAS PEMBELAJARAN MENYIMAK CERPEN DENGAN MENGGUNAKAN MEDIA REKAMAN PEMBACAAN CERPEN - Syahruddin Syahruddin (Universitas Negeri Makassar, 2022)
Improving the Quality of Learning to Listen to Short Stories by Using Short Stories Recorded Media. This research is classified as Classroom Action Research because it aims to improve the quality of learning in the classroom, both the process and learning outcomes. The subjects of this study were students of class XII IPA 2 UPT SMA Negeri 16 Bone with a total of 35 students. This research data obtained in the form of data on planning, implementation, and evaluation of research results. The technique used to collect data in this research is observation (observation), documentation, interviews and tests. The data collected were analyzed qualitatively and quantitatively. The results showed that there was an increase in the ability to listen to readings using reading reading media in students of XII IPA 2 UPT SMA Negeri 16 Bone after learning to listen to poetry using poetry reading class media in the first cycle which achieved learning completeness of 42.86% with an average score of 42.86%. average 64.86. These results increased in the second cycle by 97.14% with an average value of 87.00.